Eschatological Expression In The Holy Text (A Preliminary Hermeneutical Exploration On Selected Eschatological Narratives In The Qur’an And The Bible) - Asep Nahrul Musadad (Ar-Raniry: International Journal of Islamic Studies, 2015)
One of the key concepts that lie in almost every religion, as asserted in each holy text, is eschatological doctrine. The apocalyptic belief in the last day has existed throughout the history of civilizations with various expressions. Eschatological narrative in the holy texts ought to be deemed as a historical text that is revealed within its space and time. Accordingly, it is a historizing thing, which contains plenty of stories besides its sacred messages. This sense of historical awareness is pointed out for example by the eschatological narratives in the Qur'an which strongly influenced by socio-religious circumstances and topographical conditions in the Arabian Peninsula at the time of revelation, as the Bible that has cased up its eschatological narratives based on a certain historical event: the destruction of Jerusalem in 70 AD by Roman soldiers. The central purpose of this paper is to explore the connection and influence of certain historical moments on the style and construction of both, the Qur'an and the Bible eschatological narratives, through a simple hermeneutical analysis.